A Letter to My Newborn - McMillan, Caitilin (ACME, 2024)
This letter takes place as a conversation with my newborn about the struggles and desires I see on the horizon at the moment of writing. The letter’s simple style and straightforward language invite you to immerse yourself in an intimate sharing between myself and my one-year-old and consider the perspective of a young child coming to grips with the world around them. I draw on past conversations with my mother about her illness and her ecological work, as well as elements of our family history working and living on the river Clyde. Falling somewhere between a poem, a story and a letter, I explore themes of change and hope, ecological precarity, health and illness, and a path towards more livable worlds. Two photos included with the letter share intimate moments with the reader related to my writing – the moment Clyde reaches for his grandmother at the water’s edge, an ode to the river on which she grew up and after which he is named; and the moment my mother unfolds her hand letting an edible flower sit delicately along her hand’s life lines as an offering of nourishment and interconnection.